(untitled) (Citizen and Government Review, 2024)
Tourism in Lembanna area offers natural tourism, namely the green atmosphere of the pine forest supported by the view of the residents’ vegetable gardens. The development of pine forest tourism in Lembanna has contributed to the social and economic aspects of the community, such as their way of life and also in terms of income. This research aims to determine the social economic impacts on the community from the development of pine forest tourism. The type of research used is qualitative approach through interview and observation. Data collection was carried out through interviews and observations. The research results show that the social impact indicated is the existence of kinship relations between the community and visitors, in addition to the increased awareness of the population regarding education. However, there are also negative impacts, such as free mixing among the youth in the pine forest area due to the presence of camping tents and theft crimes. The economic impact is that the local community has additional income because they can build food stalls and equipment rental places. The government is advised to strengthen regulations and supervise activities in the Lembanna Pine Forest to minimize the negative social impacts. In addition, local community education and empowerment programs need to be improved to be better prepared to manage tourism sustainably.